2019
DOI: 10.1371/journal.pone.0218119
|View full text |Cite
|
Sign up to set email alerts
|

Depression among people living with type 2 diabetes in an urbanizing community of Nepal

Abstract: Background Diabetes mellitus is a major public health problem which accounts for serious medical and economic consequences. Depression is an important associated condition that upsets the management and complications of diabetes. This study aimed to measure the prevalence of depression among people living with Type 2 Diabetes and to examine the factors linked with it. Methods This community based, cross-sectional study was conducted among 278 people living with type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 33 publications
5
50
0
1
Order By: Relevance
“…Various studies have documented that factors associated with depression among diabetes patients using the classical logistic regression. Risk factors were age [ 10 , 15 , 34 ], gender [ 14 , 15 , 35 38 ], marital status [ 15 , 35 , 37 , 39 ], educational status [ 34 , 37 , 40 ], hazardous drinking [ 38 , 39 ], medication adherence [ 13 , 39 ], duration lived with DM [ 9 , 14 , 35 ], fasting blood sugar [ 41 ], DM complication [ 10 , 12 , 14 , 36 , 37 ], chronic illness other than DM [ 14 , 34 ], and types of medication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have documented that factors associated with depression among diabetes patients using the classical logistic regression. Risk factors were age [ 10 , 15 , 34 ], gender [ 14 , 15 , 35 38 ], marital status [ 15 , 35 , 37 , 39 ], educational status [ 34 , 37 , 40 ], hazardous drinking [ 38 , 39 ], medication adherence [ 13 , 39 ], duration lived with DM [ 9 , 14 , 35 ], fasting blood sugar [ 41 ], DM complication [ 10 , 12 , 14 , 36 , 37 ], chronic illness other than DM [ 14 , 34 ], and types of medication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the positive effects of social interaction on health have been confirmed by many studies ( 28 , 29 ). Psychologically, social interaction can help older patients with diabetes find emotional support, enhance self-efficacy and reduce psychological problems, as older patients with diabetes report more depression ( 30 , 31 ). Physically, social interaction benefits the health of older patients with diabetes by keeping them physically active.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not observe other pivotal determinants for MHD in diabetics. The determinants involved physical capability, insulin, and drug usage, ethnicity, detailed civil status (married, single, divorced, widowed), residence status (living alone, nuclear family, joint/extended living), family size, family income, pensioner status, smoking, alcohol, religion, glycaemic control, other sociodemographic and clinical health factors [8,9,11,[25][26][27]. The involved determinants in the study will potentially explain other parameters that influence MHD among elderly diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Younger diabetics are more likely to get MHD [8] while another study reported that elderly diabetics more likely to get MHD, with the increased risk of other factors present [11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation